Robust calibration of hierarchical population models for heterogeneous cell populations. (7th March 2020) - Loos, Carolin; Hasenauer, Jan
Highlights: Generalizes hierarchical population model to various distribution assumptions. Provides framework for efficient calibration of the hierarchical population model. Simulation study and application to experimental data reveal improved robustness and optimization performance. Abstract: Cellular heterogeneity is known to have important effects on signal processing and cellular decision making. To understand these processes, multiple classes of mathematical models have been introduced. The hierarchical population model builds a novel class which allows for the mechanistic description of heterogeneity and explicitly takes into account subpopulation structures. However, this model requires a parametric distribution assumption for the cell population and, so far, only the normal distribution has been employed. Here, we incorporate alternative distribution assumptions into the model, assess their robustness against outliers and evaluate their influence on the performance of model calibration in a simulation study and a real-world application example. We found that alternative distributions provide reliable parameter estimates even in the presence of outliers, and can in fact increase the convergence of model calibration.